Therapeutic efficacy of low dose (Dhaka regimen) versus high dose (Pritchard regimen) magnesium sulphate for management of eclampsia and impending eclampsia - Bhagat, Nisha; Bedi, Preet Kamal; Pal, Davinder; Saini, Arunima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare the efficacy of low dose (Dhaka regimen) vis-a vis high dose (Pritchard regimen) magnesium sulphate in management of eclampsia and impending eclampsia. Methods: The open-label, comparative study was conducted on 90 pregnant patients. They were admitted to emergency Department of Obstetrics and Gynaecology, Government Medical College, Amritsar with eclampsia or impending eclampsia. 10 patients dropped out at various stages of study and finally, 80 were enrolled and randomized (1:1 ratio) into two groups. Group-1, N=40 were given low dose MgSO4 (Dhaka regime) and Group-2, N=40 were given high dose MgSO4 (Pritchard). Termination of pregnancy was done as per Bishop’s score, gestation age, maternal and fetal status. Primary outcome measure was therapeutic efficacy of equivalence for control of seizures whereas secondary outcome was adverse side-effects of both the regimens. Results: Mean age in Group-1 was 24.90±4.02 years and that of Group-2 was 25.67±3.79 years. Antepartum eclampsia was the most common diagnosis among groups i.e., 47.5% and 55% respectively. After treatment, the seizure control was 97.5% in Group-1 and 100% in Group-2 with comparable results (????2=1.013; p=0.314). However, highly significant difference was observed among dosage of MgSO4 that was required for control of seizure (23.75±2.71 gm versus 41.35±4.76 gm; p<0.001). Group-1 showed lower incidence of side-effects that is, loss of deep tendon reflex as compared to Group-2, but neonatal outcomes were comparable in both groups. Conclusions: Low dose (Dhaka regimen) was equally effective in control of seizures as compared to high dose (Pritchard regimen) with lower incidence of side-effects.